(untitled) (Global Journal of Human-Social Science, 2024)
This article contends that addressing environmental concerns in the South African context requires acknowledgment of the intertwined issues of land grabbing littering illegal dumping and inadequate service delivery It suggests that Pentecostals as members of diverse communities should shift their focus from spiritual matters to initiatives aimed at caring for the earth Therefore the article delves into Mogale City and Rand West City Local Municipality in South Africa as a case study illustrating their contribution to the ongoing environmental degradation The increasing incidence of land grabbing in these areas poses a threat to the pollution of the Wonderfontein spruit stream which flows from Kagiso through the townships of Swanieville 1 extensions 2 and 3 and continues east of Mohlakeng township to the west of Bekkersdal township Inadequate service delivery has resulted in a backlog of waste removal leading to concerning levels of littering and illegal dumping in both municipalities Consequently the article proposes a Bosadi-Pentecostal approach to tackle the persistent environmental degradation among Pentecostals and members of the identified communities Taking an insider perspective within the Pentecostal community the proposed approach aims to raise awareness of biblical teachings and advocate for a biblical strategy to promote earth care among Pentecostals and community members in these municipalities